Two-Dimensional Ordering of Ionic Liquids Confined by Layered Silicate Plates via Molecular Dynamics Simulation - Yan, Zhifei; Meng, Dawei; Wu, Xiuling; Zhang, Xiaolong; Liu, Weiping; He, Kaihua (Journal of physical chemistry. C, 2015)
Recent experiments and computer simulation studies on nanoconfined ionic liquids (ILs) have shifted the focus from perpendicular to lateral distribution, the understanding of which is crucial for IL performance in the field of energy storage systems and tribology. In this article, the structure of 1-ethyl-3-methylimidazolium bromide, [Emim][Br], confined by a hydroxyl group functionalized surface of kaolinite plates has been studied by molecular dynamics simulation. Depending on the degree of confinement, the IL anion can pack into a two-dimensional (2D) ordered structure with square symmetry, coexisting liquid–solid phase, or liquidlike structure. The ordered structure arises from surface-induced ionic orientational preference and the driving force from confinement that supports the formation of the 2D planar structure. The flexible H-bond formed between Br and surface hydroxyl group at fixed d-spacing results in the liquidlike ordering that breaks down the electrostatic network in ILs. The influence of water addition varies when confining plates are treated differently, namely, forming large H-bonding network and small isolated oligomers for relaxed and fixed d-spacing, respectively. This work reveals additional information about the relative importance of factors like packing constraints, interaction within ILs, and selective attraction in determining the structure and dynamics of confined ILs.